MENINGKATKAN JIWA KEWIRAUSAHAAN DI KALANGAN MAHASISWA - Poniman; Muhammad Sirod (STIE St. Pignatelli Surakarta, 2020)
The aim of this research is to describe the influence of lectures on business English and entrepreneurship on the entrepreneuial spirit among university students. This deals with the five aspects of entrepreneurship spirit, namely (1) Knowledge on entrepreneurship, (2) Interest to be an entrepreneur, (3) Perception on the role of entrepreneurs in national development, (4) Toughness of being an entrepreneur and (5) Potency to be an entrepreneur. This research uses comparative method, in which the data are compared, between those taken before and after the respondents join the two kinds of lectures above. The results of the study show that (1) The students of ABA and STIE St. Pignatelli Surakarta have got the spirit of entrepreneurship with the point of 2,38; (3) The two lectures are able to increase the aspects of entrepreneurial spirit with significant point 0,96 (from 2.38 to 3.34 (2) The increase of each aspect of entrepreneurial spirit are: (a) Knowledge on entrepreneurship by 0.98 (from 2,23 to 3,21), (b) Interest to be an entrepreneur 0,83 (from 2,6 to 3,43, (c) Perception on the role of entrepreneurs in national development 0,96 (from 2,64 to 3,6, (d) Toughness of being an entrepreneur 0,94 (from 2,29 to 3,23) and (e) Potency to be an entrepreneur 0,96 (from 2,3 to 3,26).